1980
DOI: 10.1128/jvi.33.1.550-552.1980
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of BALB/c-3T3 cells by tsA mutants of simian virus 40: effect of transformation technique on the transformed phenotype

Abstract: Simian virus 40 tsA-transformed BALB/c-3T3 cells isolated as foci of overgrowth in liquid medium were compared with those isolated as colonies in soft agar. Efficiencies of transformation were equivalent in the two procedures. Cells isolated as foci were able to grow in agar and vice versa. No difference in temperature sensitivity of the transformed phenotype was detected when tsA transformants selected in agar were compared with those selected as foci. The use of the two different transformation procedures, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…A possible explanation of these clones is that they contain higher levels of the heatlabile T antigen than their heat-sensitive counterparts, as has been demonstrated for one clone of CHL cells (10,47) and one clone of 3T3 mouse cells (6). This explanation correlates with the observations that temperature-independent clones occur more frequently when rat cells are infected at a high MOI (33) or when rat cells (although not mouse) (16,29) or semipermissive CHL cells (27) are unable to grow freely immediately after infection (33,38). Our failure and that of others (11) to detect in rat cells an increased quantity of T antigen in unrestricted clones compared with restricted clones might be due to the inadequate sensitivity of quantitation by immunoprecipitation.…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…A possible explanation of these clones is that they contain higher levels of the heatlabile T antigen than their heat-sensitive counterparts, as has been demonstrated for one clone of CHL cells (10,47) and one clone of 3T3 mouse cells (6). This explanation correlates with the observations that temperature-independent clones occur more frequently when rat cells are infected at a high MOI (33) or when rat cells (although not mouse) (16,29) or semipermissive CHL cells (27) are unable to grow freely immediately after infection (33,38). Our failure and that of others (11) to detect in rat cells an increased quantity of T antigen in unrestricted clones compared with restricted clones might be due to the inadequate sensitivity of quantitation by immunoprecipitation.…”
Section: Methodssupporting
confidence: 86%
“…The tsA58 transformants are primarily heat sensitive for the maintenance of transformation, reflecting the phenotype of this mutant in the lytic cycle, whereas none of the wild type-transformed clones are heat sensitive. Concordant results have been reported for other tsA mutants and with other cell types (6,11,16,27,32,38). aFlll cells or a cold-sensitive clone of Flll cells transformed by tsA1499 were infected with various multiplicities of either wild-type virus or small t deletion mutant dll410 and assayed for transformation in soft agar at 32.5°C.…”
Section: Methodssupporting
confidence: 78%
“…Virus and cells. The propagation of BALB/c 3T3 mouse cells and their transformation by infection with tsA58 virions were performed at 33°C as we previously described (6,12). A primary focus of transformed cells was isolated in liquid medium and recloned thrice in succession at 33'C by endpoint dilution.…”
Section: Methodsmentioning
confidence: 99%
“…Expression of T antigens. Our previous studies have indicated that the presence of a functional SV40 large T antigen is required to maintain the transformed phenotype of most tsA-transformed BALB/c-3T3 cells (4,5,11). This phenomenon has been well documented in other cell lines by a number of investigators (reviewed in references 16 and 24).…”
Section: Resultsmentioning
confidence: 80%
“…Propagation of untransformed and transformed BALB/c-3T3 mouse cells was performed as previously described (2, 4). Infection of revertant 116 BENDER, CHRISTENSEN, AND BROCKMAN cells with wild-type SV40 strain 776 and selection of retransformed cells were performed as outlined for the transformation of BALB/c-3T3 cells (4,11).…”
Section: Methodsmentioning
confidence: 99%